ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENGAMBILAN SURAT CUTI KERJA BERBASIS WEB PADA UNIT PENGELOLA KEGIATAN (UPK) SADU MANDIRI KECAMATAN SADU - Yaakub, Saleh; Madhrozji, Tutuk; Ediansa, Oka (LPPM Universitas Muhammadiyah Jambi, 2022)
Design a Web -Based Information System hearts to present information about and permit in the industrial management with PHP and MySQL. The system will design, process and manage absence and permit in the corporation. Design Information System uses flow diagram modeling, and relationship diagram. Implementation from this Information System will make easy to have a Permit Decision and make be more effective and efficient process. This System will be based HTML 5, so can be accessed using a browser from all device